Shortcut nitrification and denitrification shed light on simultaneous removal of conventional contaminants and antibiotic resistance genes (ARGs). Issue 1 (February 2022) - Wang, Lin; Yang, Chong; Yang, Zhendong; Chen, Yangwu; Wang, Fan; Li, Wenwei; Li, Xin; Zhou, Houzhen; Tan, Zhouliang
Abstract: The threats of emerging pollutants like antibiotic resistance genes (ARGs) in wastewater utilities are gaining growing attention. Based on the existing wastewater treatment process (WWTPs), especially in the biological treatment units, how to remove conventional pollutants and ARGs simultaneously and efficiently is very important. We noted that driving factors of ARGs reduction highly overlaps with that controlling shortcut nitrification and denitrification (e.g., pH, free ammonia (FA), and free nitrous acid (FNA)). This was statistically confirmed by a lab-scale and pilot-scale test. On this basis, we then propose shortcut nitrification and denitrification can be a potential approach, reducing ARGs and conventional contaminants efficiently and economically. This innovative concept may provide new opportunities for ARGs reduction, and possibly renovate the present tech-map of existing wastewater treatment plants (WWTPs). Graphical Abstract: ga1 Highlights: The driving factors of ARGs reduction overlap with operating parameters in shortcut nitrification and denitrification. Shortcut nitrification and denitrification reduce ARGs and conventional pollutants simultaneously. The key to reduce ARGs dissemination is to block horizontal and vertical gene transfers based on microbial community.